Neural responses to peer rejection in anxious adolescents: Contributions from the amygdala-hippocampal complex - Lau, J; Guyer, A; Tone, E; Jenness, J; Parrish, J; Pine, D; Nelson, E (2012)
Peer rejection powerfully predicts adolescent anxiety. While cognitive differences influence anxious responses to social feedback, little is known about neural contributions. Twelve anxious and twelve age-, gender-and IQ-matched, psychiatrically healthy adolescents received "not interested" and "interested" feedback from unknown peers during a chat room task administered in a neuroimaging scanner. No group differences emerged in subjective ratings to peer feedback, but all participants reported more negative emotion at being rejected (than accepted) by peers to whom they had assigned high-desirability ratings. Further highlighting the salience of such feedback, all adolescents, independently of anxiety levels, manifested elevated responses in the amygdala-hippocampal complex bilaterally, during the anticipation of feedback. However, anxious adolescents differed from healthy adolescents in their patterns of persistent amygdala-hippocampal activation following rejection. These data carry interesting implications for using neuroimaging data to inform psychotherapeutic approaches to social anxiety. © The Author(s) 2011.